Long-term Minimum 15-Year Follow-up After Lateral Discoid Meniscus Rim Preservation Surgery in Children and Adolescents. Issue 9 (October 2021) - Lins, Laura A.B.; Feroe, Aliya G.; Yang, Brian; Williams, Kathryn A.; Kocher, Sophia D.; Sankarankutty, Saritha; Micheli, Lyle J.; Kocher, Mininder S.
Abstract : Background: Discoid meniscus is a congenital variant typically affecting the lateral meniscus of the knee. Historically, surgical intervention when symptomatic consisted of total meniscectomy; however, after degenerative changes were observed, current treatments now focus on rim preservation with arthroscopic saucerization and meniscal repair for instability, when indicated. The purpose of our study was to examine long-term patient-reported outcomes of lateral discoid meniscus (LDM) treated with meniscal-preserving techniques. Methods: Ninety-eight patients treated arthroscopically for LDM at a single institution at a minimum of 15 years ago were retrospectively identified and contacted by mailers and telephone to participate. Subjective functional outcomes and patient satisfaction data were collected using a questionnaire that included the validated International Knee Documentation Committee Subjective Knee Evaluation Form, Lysholm Score, Marx Activity Rating Scale, Tegner Activity Score, and Western Ontario and McMaster University Osteoarthritis Index Osteoarthritis Index. Patient and surgical characteristics and patient-reported outcomes were summarized by mean and SD, median and interquartile range (interquartile range), or frequency and percent, as appropriate. Results: Of the 46 patients contacted (response rate of 46/98 eligible), 25 (54%) completed the questionnaires. The mean (±SD) age at initial surgery was 10.8 (±3.4) and 30.3 (±3.7) years at final follow-up. The mean (±SD) follow-up time from initial surgery was 19.5 (±2.8) years (range, 16 to 27). Patient-reported outcomes included: International Knee Documentation Committee 77.4±17.2, Lysholm 78.6±21, Western Ontario and McMaster University Osteoarthritis Index 7.6±11.3, Tegner Activity 7 (of 10), and Marx Activity Rating Scale 8 (of 10). Eleven (44%) cases underwent subsequent LDM-related surgery on the ipsilateral knee(s). There were no cases of total knee replacement. Conclusions: Overall, patient-reported outcomes were favorable at a minimum of 15-year follow-up after rim-preserving saucerization of LDM. While two thirds of patients were satisfied with their surgical outcomes, nearly half of patients underwent revision saucerization with or without meniscal repair. Subsequent long-term follow-up studies with objective outcome measures are important to further elucidate the natural history of LDM and understand how rim-preserving procedures may prevent the development of degenerative processes. Level of Evidence: Level IV—case series, prognostic study. Abstract : Supplemental Digital Content is available in the text.